Methylmercury exposure and child malnutrition: Mechanistic pathways and epidemiological evidence - A narrative review - Davod Boanarges Hasudungan Sinaga; ST Austa Nusra; Waisaktini Margareth Malau; Prasita Ayu Widyaningtias; Roma Yuliana; Lastrie Asrya (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Mercury exposure has emerged as a public health concern that may contribute to impaired nutritional status among children, particularly in developing countries where environmental contamination remains prevalent. Purpose: To review the biological mechanisms and epidemiological evidence regarding the effects of methylmercury exposure on children's nutritional status. Method: A narrative review was conducted by synthesizing evidence from published studies on methylmercury exposure and child nutrition, focusing on gastrointestinal, metabolic, and endocrine mechanisms as well as epidemiological findings from various countries. Results: Methylmercury disrupts nutrient absorption, interferes with essential mineral metabolism, and alters endocrine function. Epidemiological studies consistently demonstrate associations between mercury exposure and stunting, anemia, impaired growth, and abnormal body mass index trajectories among children. Conclusion: Mercury exposure negatively affects children's nutritional status through multiple biological pathways. Further prospective studies are required to establish causality and inform preventive public health strategies.